Indeterminacy of Meaning in William Blake’s “The Sick Rose” - Dhungel, Nabaraj (Interdisciplinary Journal of Innovation in Nepalese Academia, 2022)
This study attempts to make deconstructive reading of William Blake’s poem “The Sick Rose”. It also shows how the literary text can be interpreted from multiple perspectives deriving infinite meanings from the same text. The major motive of this research is to demonstrate potentiality of every text to be creatively misread generating various possible meanings. The paper also projects the fact that deconstruction is not destruction, rather it is reconstruction. It displays how the use of language in the text creates contradiction, un-decidability and multiplicity opening up possibility for new meanings. To justify the argument, deconstructive ideas of the philosophers Jacques Derrida and Roland Barthes have been used. The four steps of deconstructive reading- a. Reading the Text b. Finding the Binaries c. Hierarchizing the Binaries and d. Creative Misreading-have been followed for the study of the poem “The Sick Rose”. This research can be a contributing source for promotion of deconstructive reading of anything prevailing in the society and thereby decentering the center and re-centering the margin opening up possibilities for new perspectives, meanings and truths.